Development of Smart Green City in East Sumba - Adellia Agusta; Diana Tri Astuti; Descorina Priscillia Br. Sitompul; Hubi Maria Padji; Roidah ‘Afro’; Kartika Ariaswara (PT. AVID MEDIA INDONESIA, 2026)
A rapid urbanization creates the alternative of smart green city development, specifically located in East Sumba. However, the aspects of health and alternative energy are still in low index, which could harm the sustainability of the future. This research is aimed to analyze further about the development of smart green city in alternative energy and health sector, and how it influences the aspects of life through their opportunities and challenges in East Sumba